Analisis Kondisi Temperatur Di PT. Lembah Karet - Berliani Osmeiri; Aryo Sasmita; Ivnaini Andesgur (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The production process at PT. Lembah Karet which processes raw rubber into crumb rubber is divided into wet and dry production stages. Which in the production process produces noise from the use of machines. Noise arising from the use of machines unwittingly will cause disruption of bodily functions in workers, especially in hearing loss. The purpose of this research is to know the intensity of noise resulting from the use of machines, noise mapping, evaluation of noise intensity, exposure time and noise control efforts. In this research measurements of temperature, wind speed and noise intensity using a Sound Level Meter (SLM). The results of this research found that the highest temperature reached 35,5oC and the lowest temperature reached 29 oCKeywords: Temperature, PT. Lembah Karet, Noise